BASIC SKILLS OF STUDENTS DEALING WITH THE WORLD OF WORK THROUGH ACCOUNTING PRACTICES IN SMK NEGERI 3 BANJARMASIN - Nor Amalina (JURNAL SOCIUS, 2020)
Abstract This study aims to describe the learning, media, and curriculum of the SMK Negeri 3 Banjarmasin Accounting expertise program, describe the debriefing provided by the school before the Accounting expertise program students carry out the internship and describe the experience gained by the accounting expertise program at the SMK Negeri 3 Banjarmasin accounting program from the implementation of the internship in the relevant agencies. The research method used is a qualitative research method with data collection techniques through interviews, observations, and document studies. Sources of data obtained from interviews with informants are productive accounting teachers, deputy head of the public relations department, deputy head of the curriculum, administrative staff, and students of accounting expertise program at SMK Negeri 3 Banjarmasin. Data was also obtained from the document study results. The results showed that the Banjarmasin SMKN 3 in teaching and learning activities developed a KTSP-based curriculum, as well as carrying out industrial work activities for three months while students were in the third and fourth semester, and using online learning media to support learning while students were in the business world of industry. As for debriefing by the school when the child will carry out an apprenticeship given by productive teachers, counseling guidance. the head of the expertise program, the deputy head of the school, to the head of the school regarding student matters and readiness regarding the implementation of the internship. Industrial work practices provide special experience and illustrations for students related to business and the industrial world.